Correlation between balance and the level of functional independence among elderly people - Prata, Melina Galetti [UNESP]; Scheicher, Marcos Eduardo [UNESP] (Associação Paulista de Medicina (APM), 2012)
CONTEXTO E OBJETIVOS: Como está ocorrendo um aumento do número total de pessoas idosas, há um aumento correspondente de idosos com incapacidades. Para examinar se há alguma relação entre equilíbrio e atividades de vida diária, nós avaliamos o equilíbrio e as atividades de vida diária em idosos da comunidade. TIPO DE ESTUDO E LOCAL: Estudo transversal na Universidade Estadual Paulista (Unesp), Marília, São Paulo, Brasil. MÉTODOS: O estudo incluiu 70 idosos moradores da comunidade com 65 anos ou mais de idade. O equilíbrio foi avaliado por meio da Escala de Equilíbrio de Berg (EEB) e a independência nas atividades de vida diária foi avaliada usando o Índice de Barthel (IB). O coeficiente de correlação de Spearman foi usado para examinar a relação entre os parâmetros avaliados. Foi fixado um valor significante ao nível de 5% (P < 0,05). RESULTADOS: A média de idade da população foi de 70,5 ± 5,0 anos. O escore médio da EEB foi de 50,9 ± 4,1, enquanto o do Índice Barthel foi de 98,1 ± 2,8. Uma correlação significativa foi encontrada entre os escores da EEB e o IB (r = 0,41; P = 0,0004), entre idade e Índice de Barthel (r = -0,24; P = 0,04) e entre idade e escores da EEB (r = -0,57; P = 0,0001). CONCLUSÕES: Os resultados mostraram que, em idosos, há correlação entre idade, equilíbrio e nível de independência.

CONTEXT and OBJECTIVE: As the overall number of elderly people increases there is a corresponding rise in the number of older persons with disabilities. In order to examine whether there is any relationship between balance and activities of daily living, we evaluated balance and daily activities among elderly people living in the community. DESIGN and SETTING: Cross-sectional study at Universidade Estadual Paulista (Unesp), Marília, São Paulo, Brazil. METHODS: The study included 70 community-dwelling elderly people aged 65 and over. Balance was evaluated using the Berg Balance Scale (BBS) and physical independence in daily activities was evaluated using the Barthel Index (BI). The Spearman correlation coefficient was used to examine the relationship between the parameters evaluated. Significance was set at the level of 5% (P < 0.05). RESULTS: The population's mean age was 70.5 ± 5 years. The mean BBS score was 50.9 ± 4.1, whereas the mean BI score was 98.1 ± 2.8. Statistically significant relationships were found between the BBS and BI (r = 0.41; P = 0.0004); between age and BI (r = -0.24; P = 0.04); and between age and BBS (r = -0.57; P = 0.0001). CONCLUSIONS: The results showed that among elderly people, there are correlations between age, balance and independence level.
Correlação entre o equilíbrio e o nível de independência funcional em idosos
Keywords: Envelhecimento; Equilíbrio postural; Atividades cotidianas; Vida independente; Movimento; Aging; Postural balance; Activities of daily living; Independent living; Movement